Pseudogymnoascus destructans: evidence of virulent skin invasion for bats under natural conditions, Europe - Bandouchova, H; Bartonicka, T; Berkova, H; Brichta, J; Cerny, J; Kovacova, V; Kolarik, M; Köllner, B; Kulich, P; Martínková, N; Rehak, Z; Turner, G G; et al. (Transboundary and emerging diseases, 2015)
While Pseudogymnoascus destructans has been responsible for mass bat mortalities from white-nose syndrome (WNS) in North America, its virulence in Europe has been questioned. To shed the light on the issue of host-pathogen interaction between European bats and P. destructans, we examined seventeen bats emerging from the fungus-positive underground hibernacula in the Czech Republic during early spring 2013. Dual wing-membrane biopsies were taken from Barbastella barbastellus (1), Myotis daubentonii (1), Myotis emarginatus (1), Myotis myotis (11), Myotis nattereri (1) and Plecotus auritus (2) for standard histopathology and transmission electron microscopy. Non-lethal collection of suspected WNS lesions was guided by trans-illumination of the wing membranes with ultraviolet light. All bats selected for the present study were PCR-positive for P. destructans and showed microscopic findings consistent with the histopathological criteria for WNS diagnosis. Ultramicroscopy revealed oedema of the connective tissue and derangement of the fibroblasts and elastic fibres associated with skin invasion by P. destructans. Extensive fungal infection induced a marked inflammatory infiltration by neutrophils at the interface between the damaged part of the wing membrane replaced by the fungus and membrane tissue not yet invaded by the pathogen. There was no sign of keratinolytic activity in the stratum corneum. Here, we show that lesions pathognomonic for WNS are common in European bats and may also include overwhelming full-thickness fungal growth through the wing membrane equal in severity to reports from North America. Inter-continental differences in the outcome of WNS in bats in terms of morbidity/mortality may therefore not be due to differences in the pathogen itself.
Keywords: Animals; Microscopy, Electron, Transmission; Ascomycota; Seasons; polymerázová řetězová reakce; Polymerase Chain Reaction; Chiroptera; druhová specificita; Mycoses; Species Specificity; kůže; roční období; mykózy; Skin; Czech Republic; interakce hostitele a patogenu; Česká republika; transmisní elektronová mikroskopie; zvířata; Host-Pathogen Interactions